Ethnobotanical Survey of Plants Used in the Traditional Treatment of Female Infertility in Southwestern Nigeria - Soladoye, Michael Olasunkanmi; Chukwuma, Emmanuel Chukwudi; Sulaiman, Olatunji M; Feyisola, Roseline T (Ethnobotany Research and Applications, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> An ethnobotanical survey of plants used in the traditional treatment of infertility in females in three southwestern states of Nigeria (Oyo, Ogun, and Osun) was conducted through a structured questionnaire. Herbalists, herb sellers, and aged couples were interviewed, and their responses were documented. In all, 75 plant species belonging to 41 families of angiosperms were said to be useful in the traditional management of infertility. Some of the recipes, methods of preparation, and administration were also documented.